Influence of enzymative catalysis on technological parameters of apple juice production - L. V. Gnetko; L. P. Nerovnykh; M. M. Udychak; B. B. Siyukhova; M. M. Kobleva (Новые технологии)
The article provides data on the investigation of the effect of enzymatic catalysis on the technological parameters of apple juice production. Apples are distinguished by the presence of a heterogeneous high-molecular complex of biopolymers, which complicates their processing: it prevents juice output, hinders its clarification, filterability of wine materials and negatively affects the colloidal stability of wines. Enzymatic catalysis based on the action of microbial preparations, contributes in many respects to the successful solution of the problems of intensifying technological processes of fruit and berry raw materials processing and improving the quality of obtained products. Enzyme preparations of complex action, causing deep hydrolysis of high-molecular components of the peel and pulp of fruits, provide a more complete extraction of the liquid fraction, better clarification and filterability of juices. The foothill zone of Adygea has special soil and climatic conditions that affect the formation of physical and chemical characteristics of raw materials. Considering that apple tree occupies the first place in terms of planting area among fruit crops in the Republic of Adygea, an urgent task is to study the effect of enzymatic catalysis on technological properties of juices obtained during the processing of apples grown in these soil and climatic conditions. Enzyme preparations of complex action, recommended for the processing of fruit juices and wine materials, made in France and Germany, have been selected as objects of the research. The results of the studies on the use of enzyme preparations in the processing of apple juices, taking into account their influence on the juice yield and such technological parameters as the speed and quality of clarification, filterability and dynamics of alcoholic fermentation, have been presented. The effect of enzymatic catalysis on the mass concentrations of polysaccharides, starch, total nitrogen and phenolic substances has been studied. A higher hydrolytic activity of the Extrazyme enzyme preparation has been established, when added to the pulp; it contributes to the deep transformation of high-molecular substances and, as a result, to optimize the technological parameters of juice production